Modelling and control design of vibration reduction systems : methods and procedures of selecting vibro-isolation properties /: methods and procedures of selecting vibro-isolation properties. ([2019]) - Krzyżyński, Tomasz; Maciejewski, Igor; Meyer, Lutz; Meyer, Henning, 1978-
No abstract available